The Place Of Horticulture In Uzbekistan To Eliminate Food Problems - Akhrorjon Islomjon Ogli Boyazkulov (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
Famine is a major concern in many parts of the world today. In such a complex situation, the article discusses the important and timely agrarian reforms aimed at preventing this problem and the attention paid to this area in recent years